Ethical Climate as a Mediator between Employees' Organizational Silence Behaviors and their Trust in Leader: An Empirical Research on Insurance Sector Employees - (:unkn) unknown (ARDABIL INDUSTRIAL MANAGEMENT INST, 2018)
Leaders play a major role in determining effectiveness across all organizational levels compromising (individual, team and units through their ability of ensuring trust among their subordinates and co-workers). In this study, the effect of trust in leader on employees' organizational silence behavior and ethical climate as a mediating role was investigated. In order to measure the impact of the perceptions of employees' trust in their leaders on their silence behavior particularly on defensive, acquiescent, and pro-social silence, a survey was conducted among 811 employees working in various insurance companies in Istanbul, Turkey. To test the hypotheses, hierarchical regression technique was used. According to the findings, trust in leader negatively affected silence intentions of employees. Furthermore, the findings presented a supporting evidence of the full mediating effect of ethical climate for the relation between trust in leader and overall organizational silence, and acquiescent and pro-social silence behavior. However, findings revealed that ethical climate had a partial mediating effect on the relation between trust in leader and defensive silence behavior of employees. (C) AIMI Journals
Keywords: trust in leader; organizational silence; ethical climate; insurance sector; JOB-SATISFACTION; TURNOVER INTENTION; PROCEDURAL JUSTICE; COMMITMENT; WHISTLE; MODEL; VOICE; PERFORMANCE; SUPERVISOR; ATTITUDES